Modern Lesson Forms in Mathematics in Primary Schools - Ergashovna, Saidova Gavhar (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses modern forms of mathematics lessons in the primary grades, and discusses effective ways for primary school students to master mathematics quickly and easily, in line with today’s requirements. It also reveals the methods that can be used in the organization of modern and innovative lessons, as well as the procedure for their conduct.